Stakeholders’ issues as a source of project delays: a meta-analysis between building and road projects - Mejía, Guillermo; Sánchez, Omar; Castañeda, Karen; Pellicer, Eugenio (Revista de la Construcción. Journal of Construction, 2023)
Delay is one of the most common and complex issues that adversely affect the performance of construction pro-jects. Although much research exists on project delay, only some studies have systematically summarized and compared the causes of delay by the project type. In addition, few studies have quantitatively combined the variability across studies and related them to the responsibilities of project stakeholders. This study conducted a meta-analysis to provide quantitative and reliable evidence on delay causes combining previous research. This study categorized the top ten causes of delay published in primary research studies, calculated the average aggregate relative important index (RII) of these causes, quantitatively summarized their impact on building and road projects using meta-analysis techniques, and linked them to stakeholder responsibility. Based on an initial 160 top ten-delay causes reported, the study aggregated them into sixteen factors and seven management areas. This research found a different prioritization of delays by project type. Overall, while "site management & technical processes" was the most critical delay factor for building projects, "external issue" was for road projects. The comparison by region shows that "skills, knowledge & experience" was the most critical factor for African studies, but "late delivery and material-equipment issues" was for Asian studies. These factors were related to project stakeholders for defining mitigation actions that led to better project performance. Finally, this study provides a first taxonomy of delays, where the previous causes reported in the literature were clustered into factors and management areas.